Petrogenesis of REE-rich two-mica granite from the Indosinian Xiekeng pluton in South China Block with implications for REE metallogenesis - Zhang, Defu; Lv, Tingting; Wang, Xiangaung; Cao, Mingxuan; Chen, Xiquan; Zhang, Yongwen; Gong, Liangxin (Frontiers in Earth Science, 2025)
The Xiekeng pluton, located in Huichang County, Jiangxi Province, is primarily composed of two-mica monzogranite. The rock features high contents of SiO2 (71.3–77.73 wt%), K2O (4.42–5.62 wt%), K2O/Na2O (1.36–1.87), and with an A/CNK value of 1.11–1.27, a differentiation index (DI) of 90.28–94.47, zircon saturation temperatures of 780°C–806°C, and K/Rb, Nb/Ta, and Zr/Hf ratios of 8.40–11.04, 2.38–9.24, and 25.42–35.37, respectively. It also contains peraluminous minerals such as muscovite, classifying it as a highly fractionated S-type granite. The total rare earth element (ΣREY = ΣREE + Y) contents range from 224.7 to 353.12 ppm, with a relative enrichment in light rare earth elements (ΣLREE/ΣHREY) of 1.55–5.36, and significant fractionation between light and heavy rare earth elements with (La/Yb)N = 3.36–18.48, and pronounced negative Eu anomalies (Eu/Eu* = 0.08–0.41). Zircon U–Pb dating ages of two-mica monzogranite samples are 241.2 ± 1.8 Ma and 238.3 ± 1.7 Ma, belonging to the Middle Triassic. Zircon εHf(t) values range from −14.93 to −9.12, with depleted mantle model ages (TDM2) of 1.86–2.03 Ga, and whole-rock Nd isotopic model ages (TDM2) are 1.90–1.93 Ga, indicating a source primarily from partial melting of Proterozoic continental crustal clay-rich mudstones. Based on muscovite chemistry, the average formation pressure of the Xiekeng pluton is calculated to be 8.35 kbar (∼30 km paleodepth). This suggests the pluton formed through deep melting and intrusion under a thickened crustal compressional tectonic setting. The Xiekeng pluton is rich in total rare earth elements, with abundant rare earth minerals such as apatite, monazite, xenotime, fluocerite, and bastnäsite, showing geochemical characteristics similar to those of typical Indosinian ion-adsorption REE deposit host rocks, indicating potential for the formation of ion-adsorption REE deposits.